KEPUASAN PASIEN TERHADAP LAYANAN KEPERAWATAN MASA PANDEMI DI PUSKESMAS UMBAN SARI PEKANBARU - Efliani, Destria; Amin, Suci (Jurnal Ilmiah Keperawatan, 2022)
The high mortality rate in Indonesia is influenced by the presence of comorbidities that are positive for the coronavirus, vulnerable age, and inadequate health facilities. Coupled with government policies such as physical distancing and PSBB to deal with COVID-19, for some people it has negative impacts such as anxiety, depression, and stress. The purpose of this study was to determine patient satisfaction with nursing services during the pandemic at the Umban Sari Health Center Pekanbaru. This study used a quantitative method, where the quantitative method used was non-experimental, with a Cross Sectional approach. The population in this study was 230 respondents. The sample in this study were 65 respondents. The technique used in sampling is purposive sampling, which is a sampling technique based on the criteria of the researcher. The results of the study were obtained between patient satisfaction with nursing services for the sake of good health as many as 27 respondents (54.0%). The results of statistical tests using chi-square showed that there was patient satisfaction with pandemic nursing services at the Umban Sari Public Health Center Pekanbaru (p = 0.001). It is hoped that the Umban Sari Pekanbaru Public Health Center will maintain the quality of nursing services during the pandemic.